Older persons with dementia at risk for institutionalization in eight European countries: a cross‐sectional study on the perceptions of informal caregivers and healthcare professionals. (4th August 2014) - Stephan, Astrid; Afram, Basema; Koskenniemi, Jaana; Verbeek, Hilde; Soto, Maria E.; Bleijlevens, Michel H.C.; Sutcliffe, Caroline; Lethin, Connie; Risco, Ester; Saks, Kai; Hamers, Jan P.H.; Meyer, Gabriele; et al.
Abstract Aims To explore the perceptions of informal caregivers and healthcare professionals regarding potential reasons for the institutionalization of older persons with dementia in eight European countries. Background Healthcare professionals may have an important role in facilitating informal caregivers' decision‐making regarding institutionalization. Little is known about the perceptions of informal caregivers and healthcare professionals prior to institutionalization. Design Cross‐sectional survey in eight European countries (November 2010–January 2012). Methods Healthcare professionals reported why they clinically judged persons with dementia at risk for institutionalization. Informal caregivers reported potential reasons from their perspectives. Answers were openly coded and categorized. Variation between informal caregivers and healthcare professionals was investigated (agreement on at least one potential reason per case/proportion of maximum attainable kappa). Results Judgements of healthcare professionals and informal caregivers on 1160 persons with dementia were included. A total of 22 categories emerged. Approximately 90% of informal caregivers reported potential reasons. In 41% of the cases, informal caregivers and healthcare professionals agreed on at least one reason. Discrepancy was high for potential reasons related to caregiver burden. For the most frequent categories (caregiver burden, caregiver unable to provide care, neuropsychiatric symptoms, overall deterioration, care dependency), 24–41% of the attainable kappa was achieved. Differences between countries emerged indicating more favourable agreement in Finland, Sweden and Estonia and lowest agreement in England and Spain. Conclusion Agreement between healthcare professionals and informal caregivers on potential reasons for institutionalization was low‐to‐moderate. Healthcare professionals are challenged to develop a detailed understanding of the perspectives and perceived burden of informal caregivers.